Effects of moral hazard and monitoring policy transmission - Jukka Topi (Bank of Finland, 2003)
This study discusses the effects of financial intermediation, banks' moral hazard and monitoring on monetary policy transmission in a simple model where borrowers are dependent on loans granted by banks with superior monitoring skills.As distinct from the prior literature on monetary policy transmission, this study does not regard banks' deposit funding as a reason for their special role in the monetary transmission.Instead, we focus on banks' role in monitoring their loan customers as part of financial intermediation and on the effects of monitoring on monetary policy. We find that when the intensity of monitoring is endogenous banks acting as financial intermediaries with moral hazard problems respond less to monetary policy in lending than nonintermediary lenders that only lend their own capital without moral hazard problems.We also find that in the model the lending response of intermediary banks to monetary policy depends on the ratio of their own capital to the volume of lending.The finding is fairly insensitive to the market structure of the banking sector.In the case of a monopoly bank, an increase in the bank's capital-to-loans ratio always weakens the transmission of monetary policy to bank lending.In the case of competitive banks, an increase in the capital-to-loans ratio weakens the transmission of monetary policy to aggregate bank lending, up to a critical level. Using a data set covering the Finnish banking sector in 1995-2000, we also offer some tentative empirical evidence that is broadly consistent with the model.Banks with higher capital ratios tend to respond less to changes in monetary policy.Our conclusion is that the outcome of the model might be helpful in explaining the heterogeneity of banks' responses to monetary policy, which frequently observed in the empirical literature.
URN:NBN:fi:bof-201408071685
Keywords: 330; monetary policy transmission; monitoring; moral hazard; bank lending channel